2010
DOI: 10.1021/ja906733q
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, Preparation, and Characterization of a Dipole Moment Switch Driven by Z/E Photoisomerization

Abstract: We report the results of a multidisciplinary research effort where the methods of computational photochemistry and retrosynthetic analysis/synthesis have contributed to the preparation of a novel N-alkylated indanylidene-pyrroline Schiff base featuring an exocyclic double bond and a permanent zwitterionic head. We show that, due to its large dipole moment and efficient photoisomerization, such a system may constitute the prototype of a novel generation of electrostatic switches achieving a reversible light-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 33 publications
4
70
0
Order By: Relevance
“…The ring inversions contribute to the torsion around C4C1′ while minimizing the required space and conserving the position of the center of mass of both rings during the early stage of the isomerization dynamics. In the case of ZW‐NAIP, we showed5b that they take place in both the excited‐state trajectory and the minimum energy path, indicating that they are driven by the S 1 force field and, therefore, are part of the reaction coordinate.…”
Section: Computational Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The ring inversions contribute to the torsion around C4C1′ while minimizing the required space and conserving the position of the center of mass of both rings during the early stage of the isomerization dynamics. In the case of ZW‐NAIP, we showed5b that they take place in both the excited‐state trajectory and the minimum energy path, indicating that they are driven by the S 1 force field and, therefore, are part of the reaction coordinate.…”
Section: Computational Resultsmentioning
confidence: 89%
“…For this reason, we focus on two trajectories released from the FC region with no initial kinetic energy and representing limiting cases (see below). These trajectories have been shown to successfully follow the bottom of the excited‐state potential energy valley for ZW‐NAIP 5b. For Rh it has also been shown that changing the initial condition do not qualitatively alter the character of the following molecular motion 12…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…First of all, a family of benzylidene-pyrroline derivatives was synthesized and analyzed by means of CASSCF// CASPT2 theoretical calculations. [11] However, the synthetic route used was complex and hardly adaptable for switches with different substitution groups. 10 -3 ).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] In a series of recent works, [21][22][23] we have applied quantum chemical methods in combination with molecular dynamics simulations to achieve a deeper understanding of the mechanism of photochemical rearrangement in synthetic lightdriven rotary molecular motors, which are based on overcrowded aromatic enylidenes. It is the purpose of the present work to apply advanced quantum chemical calculations of the same type as in refs.…”
Section: Introductionmentioning
confidence: 99%